Congenital Maxillary Double Lip: A Case Report - Pokhrel, Kashmira; Shrestha, Sajeev; Sharma, Shivalal (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
A double lip is an infrequent anomaly that may either be congenital or acquired. It commonly effects the upper lip with more predilection in males. Double lip may require surgical correction for aesthetic or masticatory reasons. Treatment includes excision of the mucosa and submucosal tissue that gives good result. A 19-year-old male presented with bulge under central portion of upper lip with no constriction. Surgical correction was done using an elliptical incision to remove excess mucosal tissues. Satisfactory aesthetic result was obtained with an uneventful healing.